Make your first video with iMovie 11 learn by video - Jago, Maxim (Peachpit Press, 2011)
"This innovative product uses interactive video to explain everything a beginner needs to know to create polished-looking videos with iMovie 11, from importing and organizing video files to using special effects like Green Screen, which lets you superimpose video footage of a person onto any background you want. Users will learn how to adjust the color of video clips, stabilize shakiness, and use Themes--which give a project special transitions, titles, and graphics. A major component is learning to build a movie by assembling and editing clips, and users will learn various ways to share their finished movie, such as creating a DVD and sharing online. Experienced instructor Maxim Jago presents 3 hours of exceptional quality video tutorials, complete with lesson files, assessment quizzes, and review materials."--Resource description page.
Title from resource description page (viewed Aug. 18, 2011)
Keywords: iMovie; Motion pictures -- Editing -- Data processing; Digital video; IMovie; Montage (Cinéma); Informatique; Vidéo numérique; Motion pictures; Editing; Data processing